Of mice and masks : how performing citizenship worked for a thousand years in the Venetien Republic and why the Age of Enlightenment brought it to an abupt end - Mirjam Schaub (Palgrave Macmillan, 2019)
While the plague raged in the 14th century, eradicating numerous patrician families, who used to keep the Maritime Republic alive with its unique system of office rotation and power distribution, the Venetians invented their endangered community and polity anew–with the help of a uniform white mask (larva or volto), a black hood and a three-pointed hat.